A Bibliometric Analysis of Sustainable Software Development's Contribution to Green Technology - Loso Judijanto; Usman Tahir; Nur Hakim; Weda Febriyanto (West Science Social and Humanities Studies, 2024)
This study presents a bibliometric analysis of the literature on sustainable software development and its contribution to green technology. By analyzing data from Google Scholar, this research identifies key trends, influential authors, and significant publications that have shaped the field from 1971 to 2024. The analysis reveals the increasing integration of sustainability principles within software engineering practices, emphasizing the critical role of green technologies in reducing the environmental impact of software systems. The study highlights the evolution of research focus towards energy-efficient coding, green data centers, and sustainable software frameworks, reflecting the growing importance of technology in achieving global sustainability goals. The findings also underscore the value of interdisciplinary collaboration in advancing the field, as evidenced by the diverse connections between technological, environmental, and economic themes. This research provides a comprehensive overview of the current state of sustainable software development and offers insights into future research directions that can further enhance the contribution of software engineering to environmental sustainability.